Touch Therapy untuk Optimalisasi Tumbuh Kembang Bayi - wahyu wijayati; Niki Septia (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
The golden period, the window of opportunity, and the critical period are important to note so that individual growth and development, especially babies, can be optimal; Touch therapy can be an alternative; through a combination of stimulation techniques between the benefits of physical and emotional touch including baby massage. The method used is lecture, question and answer, and demonstration of Touch therapy through baby massage. The auxiliary media used are leaflets, and oil for touch therapy through baby massage and weighing. The implementation time in the Tulungagung Region, East Java Province is from 12 August to 30 September 2022 with the stages of planning, implementing, mentoring, and evaluating 12 mothers and their babies. The results of the activity evaluation revealed that all the mothers of the babies said that after getting Touch therapy through baby massage; the baby is eating more and sleeping soundly and gaining weight. Optimizing the baby's growth and development can be pursued in addition to touch therapy through baby massage; also by fulfilling all the needs of the baby, providing stimulation, and monitoring/early detection of growth and development according to the baby's age.